Espaces, ouvertures et organes de circulation en hauteur dans l’église romane - Sébastien Biay; Annick Gagné (Bulletin du Centre d’Études Médiévales d’Auxerre)
The study of upper spaces in medieval churches calls for a multidisciplinary approach – monumental archaeology, art history, history of liturgy and of medieval text. This paper argues that a comprehensive study of the aforementioned spaces is indeed essential in order to obtain a better understanding of medieval places of worship and the society that built them. The arguments it brings forward are those expressed by a recent panel whose intention was to raise questions, compile issues and establish points of view rather than build interpretative models. The result of this is an array of observations on French, Italian, Spanish, German and Anglo-Norman buildings, dating from the 10th to the 13th centuries. The examples offered by the contributors of this panel are not representative of any trend ; rather they deal with problems in interpreting space, layouts and openings according to an intended public or use (ritual or not). The particular attention given to the regions of Aquitaine and Burgundy reveals a dynamic transformation of patterns which neatly summarizes the subject of the panel as it illustrates the plural and changing purposes of upper spaces in medieval churches and thus confirms the need to study them accordingly.